2014
DOI: 10.2131/jts.39.609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arecoline on hepatic cytochrome P450 activity and oxidative stress

Abstract: -Betel-quid use is associated with the risk of liver cirrhosis and hepatocellular carcinoma. The aim of the present work was to evaluate the impact of arecoline on human hepatic cytochrome P450 (CYP) enzymes in vitro and rat hepatic CYP enzymes, as well as the hepatic oxidative stress and liver injury of rats in vivo. The in vitro results indicated that arecoline hydrobromide (AH) has no significant effect on the activities of CYP2B, 2C9, 3A4, 1A2, 2E1 and 2D6 in human liver microsome (HLM). However, oral admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…21 Both CAT and GSH-px are enzymatic scavengers, which can promote the decomposition of H2O2 and scavenge oxygen free radicals in the body, thereby protecting cells from the toxic effects of H2O2. 22,23 Some researches indicated that the antioxygenation of drugs could reduce the ischemia-reperfusion injury (IRI). 24,25 SF is an effective antioxidant, which can inhibit oxidative stress and lipid peroxidation and increase the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…21 Both CAT and GSH-px are enzymatic scavengers, which can promote the decomposition of H2O2 and scavenge oxygen free radicals in the body, thereby protecting cells from the toxic effects of H2O2. 22,23 Some researches indicated that the antioxygenation of drugs could reduce the ischemia-reperfusion injury (IRI). 24,25 SF is an effective antioxidant, which can inhibit oxidative stress and lipid peroxidation and increase the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…oxidant enzymes (GSH) were found in the liver of rats exposed to 4 to 20 mg kg −1 d −1 of arecoline for seven consecutive days. 57 On the basis of the results obtained in our study, we have proposed a mechanism for the toxicity of arecoline (Fig. 8).…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, NAFLD is associated with elevated reactive oxygen species (ROS) production, increased free radical levels, and increased oxidative stress, which result in hepatic inflammation and fibrogenesis. The presence of arecoline, a major alkaloid found in the betel nut [51], further deteriorates this inflammatory pathway by depressing the activities of antioxidants in hepatic tissue [51] and enhancing production of ROS [51][52][53] and inflammatory cytokines such as tumor necrosis factor (TNF)-alpha and transcription factors such as nuclear factor (NF)-κB [54][55][56]. On the contrary, in the absence of NAFLD, the levels of oxidative stress, inflammatory cytokines, and free radicals are all lower, and there is also less activity of CYP isoenzymes, resulting in a less favorable environment for the toxic effects of safrole and arecoline, which might provide some explanations for the insignificant relationship between betel nut chewing and liver fibrosis among the subjects without NAFLD.…”
Section: Discussionmentioning
confidence: 99%